Research ethics in human and physical geography: ethical literacy, the ethics of intervention, and the limits of self-regulation - Schäfer, Susann (Research ethics in human geography, 2022)
The goal of ethical research is the protection of the subjects’ dignity and welfare: Neither humans nor animals should be unethically abused or harmed for scientific purposes in empirical studies. Against the background of these disciplinary developments, this chapter addresses the question of research ethics with a focus on human and physical geography. In particular, the chapter deals with the differences and commonalities of research ethics between human and physical geography. The response rate of 22% of physical geographers and 78% of human geographers already indicates that the topic of the survey research ethics received greater attention in the field of human geography compared to physical geography. Whereas human geographers clearly label research ethics as an important issue in terms of selecting the research subject, the role that ethics play here in physical geography is heterogeneous and does not reflect a clear tendency.
Gesehen am 29.01.2025